The foaming performance evaluation of fibrillated polytetrafluoroethylene and isotactic polypropylene blends. Issue 3 (May 2019) - Zhang, Yun; Xin, Chunling; Wang, Zeming; Mughal, Waqas; He, Yadong
Polypropylene (PP) foamed products have the advantages of heat and chemical resistance, but it is difficult to foam without modified PP. Traditionally, researchers have used chemical modification to increase the melt strength to improve the foaming properties of PP. In this article, we designed four kinds of screw combinations, and five regions are selected for sampling. The polytetrafluoroethylene (PTFE) and isotactic polypropylene (iPP) were blended by one-step fiber forming method, and then we tested the rheological properties and foaming properties. It is found that the rheological properties of the in situ microfiber composite are significantly improved than the iPP, and the crystallization temperature is also increased. The foaming experiment of the composite showed that the foaming performance of the composite with in situ microfiber morphology was significantly improved compared with the pure iPP performance, and the foaming temperature window of iPP was widened from 3°C to more than 6°C.